TOWARDS A SUSTAINABLE CAMPUS LANDSCAPE IN VIETNAM: A SYSTEMATIC REVIEW OF THE LITERATURE - Duc Thien, Tran; Van Ha, Dang; Thi Yen, Nguyen; Manh Hung, Chu; Thu Trang, Nguyen (Journal of Forestry Science and Technology, 2023)
Higher education institutions in different countries around the world have adopted a variety of sustainability strategies in their policies, management, and scholarly activities. However, the campus landscape has not been explored to promote sustainability. To address this gap, this paper provides a systematic and comprehensive review of the literature on the sustainable campus landscape. The various aspects outlined in this research can be used as a reference for building a sustainable campus landscape for higher education institutions in Vietnam. The results of the study indicate that a sustainable campus landscape must be expressed through five aspects including (1) Enhancing ecological functions in urban areas, (2) Promoting sustainability of landscape and habitats, (3) Supporting the educational and experiential activities, (4) Enhancing physical and mental health for people, (5) Preserving and promoting historical cultural values. As a case study, Vietnam needs a change in cognition to foster innovation toward building a more sustainable campus landscape in higher education institutions in the future. Approaches are suitable for Vietnam include (1) Taking educational goals as a premise, (2) Taking people as the center, (3) Taking sustainable ecology as the foundation, (4) Taking science and technology as the mainstay, (5) Taking culture, history, and aesthetics as the identity.